2022
DOI: 10.1016/j.cpcardiol.2021.100933
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19) and Severe Pericardial Effusion: From Pathogenesis to Management: A Case Report Based Systematic Review

Abstract: The Severe acute respiratory syndrome coronavirus-2 (SARS-COV-2) created a global pandemic that continues to this day. In addition to pulmonary symptoms, the virus can have destructive effects on other organs, especially the heart. For example, large pericardial effusion has been observed as a critical and life-threatening finding in Coronavirus disease of 2019 (COVID-19) patients. In this case report based systematic review, we review the reports of moderate to severe pericardial effusion associated with tamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 40 publications
(69 reference statements)
0
35
0
Order By: Relevance
“…These include direct viral injury to the myocardium, extending to the pericardium; activation of exaggerated inflammatory response to the viral infection with secondary myocardial and pericardial involvement; acute respiratory distress syndrome, resulting in cardiac hypoxic injury extending to the pericardium; or hypoxia causing pulmonary hypertension, leading to pericardial effusion. 8 , 10 Mechanisms related to secondary injury are implied by our data, showing pericardial effusion in patients with COVID‐19 infection is strongly associated with worse pulmonary disease and RV dysfunction, as well as with elevated BNP. Thus, we believe that a pericardial effusion is usually a surrogate marker of more severe COVID‐19 infection.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…These include direct viral injury to the myocardium, extending to the pericardium; activation of exaggerated inflammatory response to the viral infection with secondary myocardial and pericardial involvement; acute respiratory distress syndrome, resulting in cardiac hypoxic injury extending to the pericardium; or hypoxia causing pulmonary hypertension, leading to pericardial effusion. 8 , 10 Mechanisms related to secondary injury are implied by our data, showing pericardial effusion in patients with COVID‐19 infection is strongly associated with worse pulmonary disease and RV dysfunction, as well as with elevated BNP. Thus, we believe that a pericardial effusion is usually a surrogate marker of more severe COVID‐19 infection.…”
Section: Discussionmentioning
confidence: 75%
“…Other publications have dealt with the prevalence and clinical impact of pericardial effusion in acute COVID‐19 infection. 6 , 8 , 9 , 10 However, all these reports were either retrospective or based on systematic literature review, assessing only patients with clinically indicated echocardiographic examinations. Our study used a prospectively defined protocol and included unselected hospitalized patients encompassing all grades of disease severity, which can better evaluate the prevalence and clinical impact of pericardial effusion in hospitalized patients with COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 has been associated with hemorrhagic pericardial effusions in recent literature [3][4][5]. The mechanism of the hemorrhagic effusion is hypothesized to be due to direct cardiomyocyte and pericardium invasion by binding of the angiotensin-converting enzyme-2 (ACE2) receptor that promotes inflammation, cytokine release, fibrosis, vasoconstriction, and oxidative stress in the setting of adult respiratory distress syndrome (ARDS) [6]. SARS-CoV-2 infection is initiated by viral binding to ACE2 receptors embedded in the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 has been frequently implicated in respiratory diseases after the WHO declared the SARS-CoV-2 pandemic in early 2020. As the novel virus has been studied further over the past two years, it has been linked to diseases of other organ systems as well [1]. We now know and are continuing to discover the extrapulmonary manifestations of COVID, some of which are neurological, psychiatric, cardiovascular, gastrointestinal, renal, and integumentary in nature [1].…”
Section: Introductionmentioning
confidence: 99%